Photoluminous Response of Biocomposites Produced with Charcoal - Delatorre, Fabíola Martins; Cupertino, Gabriela Fontes Mayrinck; Pereira, Allana Katiussya Silva; de Souza, Elias Costa; da Silva, Álison Moreira; Ucella Filho, João Gilberto Meza; Saloni, Daniel; Profeti, Luciene Paula Roberto; Profeti, Demetrius; Dias Júnior, Ananias Francisco (Polymers, 2023)
Due to the possible effects of global warming, new materials that do not have a negative impact on the environment are being studied. To serve a variety of industries and outdoor applications, it is necessary to consider the impact of photoluminosity on the performance of biocomposites in order to accurately assess their durability characteristics and prevent substantial damage. Exposure to photoluminosity can result in adverse effects such as discoloration, uneven surface, loss of mass, and manipulation of the intrinsic mechanical properties of biocomposites. This study aims to evaluate general charcoal from three pyrolysis temperatures to understand which charcoal is most suitable for photoluminosity and whether higher pyrolysis temperatures have any significant effect on photoluminosity. Porosity, morphology, Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy of charcoal were analyzed. Charcoal obtained at a temperature of 800 °C demonstrates remarkable potential as a bioreinforcement in polymeric matrices, attributable to its significantly higher porosity (81.08%) and hydrophobic properties. The biocomposites were characterized for flexural strength, tensile strength, scanning electron microscopy (SEM), FTIR, and x-ray diffraction (XRD). The results showed an improvement in tensile strength after exposure to photoluminosity, with an increase of 69.24%, 68.98%, and 54.38% at temperatures of 400, 600, and 800 °C, respectively, in relation to the treatment control. It is notorious that the tensile strength and modulus of elasticity after photoluminosity initially had a negative impact on mechanical strength, the incorporation of charcoal from higher pyrolysis temperatures showed a substantial increase in mechanical strength after exposure to photoluminosity, especially at 800 °C with breaking strength of 53.40 MPa, and modulus of elasticity of 4364.30 MPA. Scanning electron microscopy revealed an improvement in morphology, with a decrease in roughness at 800 °C, which led to greater adhesion to the polyester matrix. These findings indicate promising prospects for a new type of biocomposite, particularly in comparison with other polymeric compounds, especially in engineering applications that are subject to direct interactions with the weather.